2021
DOI: 10.3390/v13102054
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis for Genes Associated with Small Ruminant Lentiviruses Infection in Goats of Carpathian Breed

Abstract: Small ruminant lentiviruses (SRLV) are economically important viral pathogens of sheep and goats. SRLV infection may interfere in the innate and adaptive immunity of the host, and genes associated with resistance or susceptibility to infection with SRLV have not been fully recognized. The presence of animals with relatively high and low proviral load suggests that some host factors are involved in the control of virus replication. To better understand the role of the genes involved in the host response to SRLV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…Consistent with our nding, ACOT4 has also been identi ed as a signi cant gene for chronic subclinical mastitis in Norwegian Red cattle [72]. The up-regulated expression of TMEM53 has been identi ed in the blood of goats with a potential role in Small ruminant lentiviruses infection [73]. The involvement of these DEGs in subclinical mastitis or other infectious diseases suggests their possible roles in immune responses and highlights their potential as biomarkers for subclinical mastitis which deserves further investigation.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with our nding, ACOT4 has also been identi ed as a signi cant gene for chronic subclinical mastitis in Norwegian Red cattle [72]. The up-regulated expression of TMEM53 has been identi ed in the blood of goats with a potential role in Small ruminant lentiviruses infection [73]. The involvement of these DEGs in subclinical mastitis or other infectious diseases suggests their possible roles in immune responses and highlights their potential as biomarkers for subclinical mastitis which deserves further investigation.…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were reported by Olech et al . ( 127 ), who showed that genes belonging to the toll-like family ( TLR2 , TLR4 , TLR7 and TLR8 ) were significantly upregulated in infected Carpathian breed goats compared to uninfected animals. Furthermore, another study conducted by Olech et al .…”
Section: Tropism and Pathologymentioning
confidence: 99%
“…Consistent with our finding, ACOT4 has also been identified as a significant gene for chronic subclinical mastitis in Norwegian Red cattle [ 74 ]. The up-regulated expression of TMEM53 has been identified in the blood of goats with a potential role in small ruminant lentiviruses infection [ 75 ]. The involvement of these DEGs in subclinical mastitis or other infectious diseases suggests their possible roles in immune responses and highlights their potential as biomarkers for subclinical mastitis which deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%